RES-360 Degree Tool Kit - Resilience in Education Systems : Rapid Assessment Manual - World Bank (Washington, DC, 2014)
One of the Education Resilience Approaches (ERA) programs first major tools, the Resilience in Education System (RES) 360 degree rapid assessment helps both national education institutions (e.g. Ministries of Education) and schools to identify the risks confronting education communities, especially students. It also points to the assets and positive engagement in school and communities that, if recognized and supported, can make national education programs more relevant and effective in contexts of adversity. This tool kit serves as a complement to the RES-360 degree manual. It contains resources for collecting and analyzing data on education resilience in a country, and for reporting and mobilizing this knowledge.